Giant magnetostructural coupling in Gd2/3Ca1/3MnO3 - Correa V. F.; Sänger N.; Jorge G.; Nieva G.; Haberkorn N.; Haberkorn, Néstor; Correa, Víctor Félix; Nieva, Gladys (IOP Publishing, 2009)
Fil: Correa, V. F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina